Scholarly Learning of Teacher-Scholars Engaging in Interdisciplinary Education - van Goch, Merel; Lutz, Christel (Journal of Interdisciplinary Studies in Education, 2023)
Many higher education institutions have put interdisciplinary teaching and learning high on their agenda. We know students learn a lot from interdisciplinary education, and we know scholars learn from their educational scholarship, but what do scholars learn from engaging in interdisciplinary education? I interviewed seven mid-career scholars about what they learned and in what ways their work was appreciated. The findings illustrate that scholars learn about education, students, interdisciplinarity, their own discipline, the university, and themselves and that the scholars felt their efforts were recognized by their interdisciplinary contexts but not rewarded outside of those contexts. The study describes academic and personal struggles, pleasures, and joys of scholars starting to engage in interdisciplinary education.